Intracellular availability of unmodified, phosphorothioated and liposomally encapsulated oligodeoxynucleotides for antisense activity. - Thierry, A R (1992)
We have studied factors which may effect the intracellular availability of oligonucleotides to achieve antisense activity. 15-20 mer unmodified, phosphorothioate modified and liposomally encapsulated oligodeoxynucleotides have been tested in leukemia MOLT-3 cells. Phosphorothioate analogs penetrated and accumulated intact in cells in contrast to unmodified oligomers, which showed a high instability in cell culture medium. A slow decrease of intracellular concentration of undegraded phosphorothioate oligodeoxynucleotides was observed after cell treatment and could be predominantly explained by a significant efflux transport. Using laser-assisted confocal microscopy we have observed that fluorescein 5-end-labeled phosphorothioate derivatives predominantly distributed in intracytoplasmic endocytic vesicles following cell treatment. The end-capped version of phosphorothioate oligodeoxynucleotides exhibited greater cellular uptake than fully modified analogues while exhibiting similar biological stability. Liposome encapsulation made possible oligomer protection in serum-containing medium and substantially improved cellular accumulation. Furthermore, the efflux rate of oligomer initially introduced within liposomes is 2-fold lower than that observed in cells which have been incubated with free oligonucleotides. Liposomal preparations of oligodeoxynucleotides facilitate release from endocytic vesicles, and thus, cytoplasmic and nuclear localization are observed following cell treatment. Furthermore, intracellular distribution studies demonstrate that intracellular transport of unmodified oligomers is effectively achieved using the liposomal carrier.